Fear of cancer recurrence among caregivers of adolescents with malignant bone tumors in China: a cross-sectional survey - Xuan, Ye-jing; Ye, Qun; Ren, Ying; Yao, Yu-hong; Wang, Zhan; Feng, Xiu-qin (Frontiers in Public Health, 2025)
BackgroundFear of cancer recurrence (FCR) is not only present in cancer patients, but also in their caregivers, and caregivers' fear of cancer recurrence is greater than that of cancer patients. The purpose of this study was to explore the current status of cancer recurrence fear and the factors influencing it among caregivers of adolescents with malignant bone tumors, and to provide a theoretical basis for the development of effective interventions in the future.MethodsA total of 249 caregivers of adolescents with malignant bone tumors were selected for this study from two hospitals in Hangzhou, Zhejiang Province, from March 2023 to March 2025. The survey was conducted using the demographic questionnaire Fear of Progression Questionnaire – Short Form/Caregiver Version (FoP-Q-SF/C), the Simple Coping Style Questionnaire (SCSQ), and the Family Hardiness Index (FHI). Factors influencing FCR in caregivers of adolescents with malignant bone tumors were determined by univariate and logistic regression analyses.ResultsThe mean score for the FoP was 35.38 ± 7.66, and 62.2% (n = 155) of caregivers had high levels of fear of cancer recurrence. Logistic regression analyses showed that female sex [odds ratio (OR) = 2.690, 95% confidence interval (CI): 1.187–6.098, P = 0.018], living in a rural area (OR = 2.450, 95% CI: 1.199–5.009, P = 0.014), burden of care (OR = 2.832, 95% CI: 1.649–4.863, P < 0.001), economic burden (OR = 2.207, 95% CI: 1.079–3.810, P = 0.004), family hardiness index (OR = 0.857, 95% CI: 0.787–0.932, P < 0.001) and positive coping style (OR = 0.887, 95% CI: 0.806–0.976, P = 0.014) had independent influences on FCR.ConclusionsFCR is a huge burden for caregivers of adolescents with malignant bone tumors. Healthcare professionals should adopt targeted disease-related health education for caregivers, help caregivers enhance the family hardiness index, guide caregivers to adopt positive coping styles, and increase caregivers' confidence in facing cancer, thereby reducing the FCR.